Modified SERVQUAL model and effects of customer attitude and technology on customer satisfaction in banking industry: mediation, moderation and conditional process analysis - Ahmed, Rizwan Raheem; Vveinhardt, Jolita; Štreimikienė, Dalia; Ashraf, Muhammad; Channar, Zahid Ali (Journal of Business Economics and Management, 2017)
Banks are very important financial services sector, and in banking sector there is an intense competition amongst the local and foreign banks throughout the world. The objective of this research is to analyse the effects of perceived value and customer trust, and role of technology in banking service qualities and customers’ satisfaction in Pakistani context. For this purpose we employed modified SERVQUAL model with four dimensions such as empathy, competence, reliability, and online service. An adapted questionnaire was used to carry out this survey research, and collected 830 responses from the customers of Pakistani banking industry. We used factor analysis, confirmatory factor analysis, and bootstrapping methods to carry out this research. The results of the study demonstrated that our four-dimensional model of modified SERVQUAL has a significant impact on overall customer satisfaction. It is further concluded from the bootstrapping method that modified SERVQUAL dimensions and customer satisfaction are positively mediated by the perceived value and trust. Finally, it is also concluded that the implementation of technology serves as moderating variable in the banking sector. The outcomes of this research are beneficial to the senior management of banking sector in order to implement the effective and customised online banking structure to gain competitive advantages, and provide vibrant online banking services that enhance the standard and ease of services to the customers and earn their confidence. The originality and novelty of this research provide a significant contribution in the application of SERVQUAL model specifically for the banking service quality dimensions and customer satisfaction in marketing research.